DETERMINAN KEPUTUSAN PEMBELIAN DITINJAU DARI SOCIAL COMMERCE, INFLUENCER, ELECTRONIC WORD OF MOUTH DAN PEMBAYARAN DIGITAL - Cahyani, Debby Tri; Suarantalla, Ryan (Samalewa: Jurnal Riset & Kajian Manajemen, 2023)
This research aims to examine the influence of Social Commerce, Influencers, Electronic Word of Mouth and Digital Payments on Purchasing Decisions in UMKM Samota Car Free Day. The sampling technique in this research uses purpose sampling, where the sample is the general public who make purchases at Car Free Day Samota, make purchases using digital payments, have social media and get information about Car Free Day Samota on social media. The data analysis techniques used are classical assumption testing, multiple regression analysis, and hypothesis testing. The type of data used is quantitative data obtained from primary data sources, then processed using the SPSS version 22 application. The results of this research are 1) Social Commerce partially has a positive and significant influence on purchasing decisions, 2) Influencers partially have a positive and significant influence on purchasing decisions, 3) Electronic Word of Mouth partially has a positive and significant effect on purchasing decisions, 4) Digital payments partially have a negative and significant effect on purchasing decisions, and 5) Simultaneously social media marketing, influencers, electronic word of mouth and digital payments have a positive and significant effect on purchasing decisions.